Low-Abundant Microorganisms: The Human Microbiome’s Dark Matter, a Scoping Review - Cena, Jéssica Alves de; Zhang, Jianying; Deng, Dongmei; Damé-Teixeira, Nailê; Do, Thuy (Frontiers in Cellular and Infection Microbiology, 2021)
Research on the human microbiome has mainly been restricted to the identification of most abundant microbiota associated with health or disease. Their abundance may reflect their capacity to exploit their niche, however, metabolic functions exerted by low-abundant microrganisms can impact the dysbiotic signature of local microbial habitats. This scoping review aims to map the literature regarding the management of low-abundant microorganisms in studies investigating human microbiome samples. A systematic literature search was performed in 5 electronic databases, as well as grey literature. We selected clinical microbiome studies targeting human participants of any age, from any body site. We also included studies with secondary data which originated from human biofilm samples. All of the papers used next-generation sequencing (NGS) techniques in their methodology. A total of 826 manuscripts were retrieved, of which 42 were included in this review and 22 reported low-abundant bacteria (LB) in samples taken from 7 body sites (breast, gut, oral cavity, skin, stomach, upper respiratory tract (URT), and vagina). Four studies reported microbes at abundance levels between 5 and 20%, 8 studies reported between 1 and 5%, and 18 studies reported below 1%. Fifteen papers mentioned fungi and/or archaea, and from those only 4 (fungi) and 2 (archaea) produced data regarding the abundance of these domains. While most studies were directed towards describing the taxonomy, diversity and abundance of the highly abundant species, low-abundant species have largely been overlooked. Indeed, most studies select a cut-off value at <1% for low-abundant organisms to be excluded in their analyses. This practice may compromise the true diversity and influence of all members of the human microbiota. Despite their low abundance and signature in biofilms, they may generate important markers contributing to dysbiosis, in a sort of ‘butterfly effect’. A detailed snapshot of the physiological, biological mechanisms at play, including virulence determinants in the context of a dysbiotic community, may help better understand the health-disease transition.